2019
DOI: 10.1590/rbz4820170177
|View full text |Cite
|
Sign up to set email alerts
|

Influence of forage production area, concentrate supply, and workforce on productive results in milk production systems

Abstract: This study aimed to investigate the influence of forage production area, concentrate supply, and farm labor on characterization of milk production systems (MPS) and their productive results. Milk volume data provided in 2014 by 110 dairy farms located in the eastern region of Santa Catarina State, Brazil, were obtained from a dairy industry. Forty-four farms with different production levels were selected, in which interviews were carried out aiming to characterize the management practices related to forage pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
(19 reference statements)
0
7
1
3
Order By: Relevance
“…Si bien se han utilizado distintas variables para la tipificación de unidades de producción, las que mejores resultados aportan para el análisis de los sistemas de producción de leche son el tamaño de la unidad de producción y el nivel de producción (9) . Este método de análisis, en la actualidad, es uno de los más empleados, como queda evidenciado en recientes estudios de caso de Brasil, Colombia y México (10)(11)(12)(13) , debido a que permite encontrar más relaciones entre las variables estudiadas. Lo anterior tiene especial relevancia debido a que la producción de lácteos se lleva a cabo en todas las regiones agroecológicas del país y se tienen desde las altamente tecnificadas hasta las de subsistencia (12) .…”
Section: Introductionunclassified
“…Si bien se han utilizado distintas variables para la tipificación de unidades de producción, las que mejores resultados aportan para el análisis de los sistemas de producción de leche son el tamaño de la unidad de producción y el nivel de producción (9) . Este método de análisis, en la actualidad, es uno de los más empleados, como queda evidenciado en recientes estudios de caso de Brasil, Colombia y México (10)(11)(12)(13) , debido a que permite encontrar más relaciones entre las variables estudiadas. Lo anterior tiene especial relevancia debido a que la producción de lácteos se lleva a cabo en todas las regiones agroecológicas del país y se tienen desde las altamente tecnificadas hasta las de subsistencia (12) .…”
Section: Introductionunclassified
“…Other studies achieved similar results. Koerich et al (2019), using similar methods to analyze dairy systems in Paraná State, found a positive relationship between variables related to forage production area and concentrate supply and dairy system productivity. They also found a positive relationship between sociodemographic characteristics of dairy farmers and productivity parameters.…”
Section: Multiple Linear Regression Of Extracted Factorsmentioning
confidence: 98%
“…After the analytical procedures, 14 variables were maintained in the analysis (Table 1). Factors were named according to the variables that defined them (Koerich et al, 2019).…”
Section: Exploratory Factor Analysismentioning
confidence: 99%
See 2 more Smart Citations